Las relaciones Socio-Afectivas para superar la timidez en las niñas y niños de 4 a 5 años de edad, del Centro de Desarrollo Infantil Abendaño Children´s School de la Ciudad de Loja. Período 2014-2015 - Romero Feijoo, Karla Maribel (2016)
The present descriptive investigation named: Social-Afective relations to overcome shyness in girls and boys from 4 to 5 years old, from the Child Development Center Abendaño Children's School of the city of Loja. Period 2014-2015, was developed according to the Academic Regulations of the National University of Loja. In this research work the general objective was to analyze the Social-Afective relations to overcome shyness in girls and boys from 4 to 5 years old. I used the following methods: scientific, inductive, deductive, descriptive and statistical and analytic- synthetic. The techniques that were used were: a observation sheet which was applied to 25 children and the interview to 2 teachers. Based on the collected data; 96 % of children like to participate in social-dramatic games and activities and often students participate voluntarily, they show security and confidence in themselves. As a conclution I can state that because of the taken social-affective activities it was possible to decreasr the level of shyness in children. I recommended to the teachers of the educational center to make socio-affective activities to support the children and at the same time motivate them to face the social situations to overcome the shyness